The Practice of Flaming Football Supporters on Ganjar Pranowo's Instagram Account - Hildansyah, Irdan; Hkikmat, Mahi M. (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2023)
FIFA (the Federation Internationale de Football Association) withdrew Indonesia from hosting the World Cup U-20 2023. This cancellation caused many peoples to be disappointed. Indonesian national team supporters expressed disappointment in Ganjar Pranowo's Instagram comments because of his stance and statement regarding his refusal of the Israeli national team to compete in Indonesia. This research explores the behavior of Indonesian football fans on Instagram using the SIDE model. This research uses netnography or virtual ethnography because this research focuses on activities in cyberspace. In cyberspace, there is a term called cyberculture. The flaming practice was not come up from a heated debate, but the flaming comments have been keen since users visited Ganjar Pranowo's Instagram account, not creating a space for discussion. Excessive fanaticism or lack of self-control sometimes makes users become actors in flaming production. In addition, anonymity is also a factor in deindividuation occurs. Flaming behavior was found when the apparent norm of previous commenters was being flamed. This research focuses more on the process of user deindividuation using the SIDE model; since this research was conducted in cyberspace, further research can be conducted offline to investigate this behavior.